Associations Between Sugars Intakes and Urinary Sugars Excretion and Carbon Stable Isotope Ratios in Red Blood Cells as Biomarkers of Sugars Intake in a Predominantly Māori Population - Te Morenga, Lisa; Kruimer, Devonia; McLean, Rachael; Sabadel, Amandine J. M.; van Hale, Robert; Tatin, Xavier; Hindmarsh, Jennié Harre; Mann, Jim; Merriman, Tony (Frontiers in Nutrition, 2021)
Determining the extent to which added sugars intake contribute to non-communicable disease in various populations is challenging because it is difficult to accurately measure intakes. Biomarkers may provide a reliable and easily measured method of assessing intakes. In a predominantly Māori population we compared various sugars intake estimates derived from a 36 item sugar-specific food frequency questionnaire (FFQ) with biomarkers of sugars intake; urinary sugars excretion in random spot collections (n = 153) and carbon stable isotope ratios (n = 36) in red blood cells (RBCs, δ13CRBC) and in the alanine fraction of the RBCs (δ13Calanine). Estimated 24 h urinary sucrose+fructose excretion was statistically significantly correlated with intakes of total sugars (r = 0.23), sucrose (r = 0.26) and added sugars from sugar-sweetened beverages (SSBs; r = 0.26). δ13Calanine was correlated with added sugars (r = 0.40). In log linear multiple regression models adjusted with HbA1C and eGFR δ13Calanine predicted added sugars intakes (r2 = 0.29) and estimated 24 h urinary sucrose+fructose excretion predicted intakes of total sugars (r2 = 0.14), sucrose (r2 = 0.17), added sugars (r2 = 0.17) and sugars from SSBs (r2 = 0.14). These biomarkers have potential for improving assessment of sugars intake in New Zealand populations enabling monitoring of the effectiveness of sugar reduction strategies designed to reduce risk of NCDs. However, further validation is required to confirm these preliminary findings.